Switzerland : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation outlines that the growth of the Swiss economy has gathered pace, but inflation remains close to zero. The recovery is expected to continue and inflation should rise gradually although the output gap will progressively close. The fiscal position is healthy, with a broadly neutral stance projected for 2014. Despite improved market confidence toward the euro area and tapering in the United States, the exchange rate has remained close to the floor. The authorities have taken several measures to contain risks, including raising the countercyclical capital buffer and adopting prudential measures to tighten lending standards and conditions.